Définir les expats : le cas des immigrés hautement qualifiés à Bruxelles - Emanuele Gatti (Brussels Studies)
More and more attention is put by sociologists on the relation between cities, development and the activities and profiles of the people attracted by cities themselves. Brussels is a particularly vivid example of this relation, being so influenced by the massive percentage of European high-level migrants, called Expats, who live there on a temporary or a permanent basis. The article, besides trying to define what an Expat is, provides an exploratory outline of how they are perceived and they perceive themselves. Moreover, the article analyses their sense of community, showing that speaking of a coherent Expats’ community, as it is commonly done by Brussels’ institutions, might be quite imprecise.